Teaching english communicative skills in preschool children - Herrnández Hernández, Helen Lizet; Luna Alfaro, Maria de Lourdes (Perspectivas Docentes, 2025)
Foreign language teaching as English has taken on importance in every current educational level and has caused interest in knowing the right age to study claiming that children are able to learn faster than adults and that an early teaching of English brings a lot of benefits in their education, growth and develop of the communicative skills, but to achieve this benefits first a teaching must be given that is suitable for the age and each of the students’ skills. From a theoretical analysis it is presented information about if age plays an important role in the teaching-learning of a foreign language, also it was analyzed authors that deal with topics about the acquisition of the language, the improvement of the accent and the importance of the appropriate use of methodologies to grant learning and to give the necessary tools for the continuous study of this language. This article showed the results of a qualitative investigation and a descriptive analysis obtained from an interview to English teachers of preschool level, these results were classified by categories in which teaching of English is approached from teaching experience.